Answer :

AmandaR84

Answer:

13/36 and 3/16

Step-by-step explanation:

1/4(1−2/3)^2+1/3  

Remember to use the oder of operations. So what is in the ( ) is first.

1/4[tex](\frac{1}{3} )^{2}[/tex] + 1/3   Now take [tex](\frac{1}{3} )^{2}[/tex] which is [tex]\frac{1}{3} *\frac{1}{3} = \frac{1}{9}[/tex]

So now we have

[tex]\frac{1}{4} *\frac{1}{9} +\frac{1}{3}[/tex]     Order of operations so we multiply next.

[tex]\frac{1}{4} *\frac{1}{9} = \frac{1}{4*9} = \frac{1}{36}[/tex]

[tex]\frac{1}{36} +\frac{1}{3}[/tex]   We need to find a common denominator to add them. 3 goes into 36 so we multiply [tex]\frac{1}{3} * 12 = \frac{1}{3} * \frac{12}{12} = \frac{12}{36}[/tex]

Now we can add them.

[tex]\frac{1}{36} + \frac{12}{36} = \frac{13}{36}[/tex]

1/3(1−1/4)^2

[tex]\frac{1}{3} (1-\frac{1}{4} )^{2}[/tex]

[tex]\frac{1}{3} (\frac{3}{4} )^{2}[/tex]

[tex]\frac{3}{4} *\frac{3}{4} = \frac{9}{16}[/tex]

[tex]\frac{1}{3} *\frac{9}{16} = \frac{9}{48}[/tex]

We can reduce 9/48 by dividing by 3/3 which equals

3/16

Other Questions